IMPLEMENTASI PENANGANAN KONFLIK SOSIAL DI LUWUK KABUPATEN BANGGAI - Fitriani Abdullah (Sekolah Tinggi Pariwisata Mataram, 2021)
This research aims to find out and describe the Implementation of Social Conflict Management Policies in Luwuk, Banggai Regency. The usefulness of this research is theoretical and practical. In the Literature Review explains the Concept of Public Policy. Thinking Flow of the theory of Van Meter and Van Horn which includes the factors of Standards and Objectives, Resources, Characteristics of Implementing Agents, Inter-Organization Communication, Socio-Economic and Political Environment, and Implementor Disposition. research with qualitative methods, Research Location of Luwuk City, Banggai district, Research time for three months, Informant is an element of Banggai district FORKOPIMDA, Devinisi Operational Concept related to the implementation model of the policy. Qualitative data types, and data sources namely Secondary data and Primary Data. The discussion explained, explicitly about the Implementation of Social Conflict Management in Luwuk Banggai district, and concluded that the Social Conflict Management Policy in Luwuk, Banggai Regency, was fully well underway. Only in implementing the policy does not involve representatives of the traditional institutions in conflict, after the results of the crucial policy of repatriating the families of the perpetrators, the regional government is deemed not to uphold Pancasila (Pancasilais) and the Constitution of the Republic of Indonesia. There must be involvement of representatives from indigenous peoples. Determination of policies needs to be revised again, studied more deeply and extensively, and looks for the best solutions for the families of the perpetrators, as well as providing compensation to residents who are repatriated.